Direct-Write Fabrication of Flexible Array Pressure Sensor for Monitoring Position Distribution. (11th September 2020) - Chen, Xiaojun; Mo, Deyun; Lian, Haishan; Gong, Manfeng; Luo, Yihui; Xia, Xiaoqun; Jiang, Shuzhen
Abstract : Tactile sensors with high flexibility have attracted great interest because of their huge potential in various applications including smart robots, smart prostheses, human-machine interfaces, and biological monitoring electronic devices. However, it remains a critical challenge to develop tactile sensors with both high sensitivity and flexibility. In this work, a flexible 8 × 8 array pressure sensors with GNPs/MWCNT filled conductive composite material on PDMS substrates was proposed using direct-write printing. The printing technology based on the Weissenberg effect had the advantages of rapid supply of fluid and avoiding needle clogging in the printing process, which was suitable for large-area manufacturing of sensor sensitive units. The sensitivity of PDMS-based flexible array pressure sensors in the pressure range of 0–25 kPa and 25–75 kPa reached ∼5.09 MPa −1 and ∼0.0209 kPa −1, respectively. Response/recovery time reached ∼150 ms and ∼200 ms, respectively. When 1000 cycles were performed in the 0–75 kPa pressure range, the PDMS substrate flexible array pressure sensor had high stability and repeatability. These superior properties are indicative of their great potential in applications such as intelligent robotics, artificial palpation, prosthetics, and wearable devices.